Transcriptome analysis of nitrogen assimilation preferences in Burkholderia sp. M6-3 and Arthrobacter sp. M7-15 - Liu, Ran; Qin, Hongyi; Wang, Qian; Chu, Cheng; Jiang, Yunbin; Deng, Huan; Han, Cheng; Zhong, Wenhui (Frontiers in Microbiology, 2025)
IntroductionAmmonium (NH4+) and nitrate (NO3−) are the two main forms of inorganic nitrogen (N) that exist in soil and both can be absorbed and utilized by plants. As a vast and crucial biome, soil microorganisms are responsible for mediating the inorganic N assimilation process and enhancing nitrogen use efficiency. Understanding how these microorganisms assimilate different forms of inorganic nitrogen is crucial. There are a handful of microorganisms that play a dominant role in the process of soil inorganic nitrogen assimilation and have a significant advantage in abundance. However, microbial preferences for ammonium or nitrate, as well as differences in their metabolic pathways under co-existing ammonium and nitrate conditions, remain unclear.MethodsIn this study, two microbial strains with nitrogen assimilation advantages, Burkholderia sp. M6-3 and Arthrobacter sp. M7-15 were isolated from an acidic Chinese soil and then incubated by different sources of inorganic N to investigate their N preferences. Furthermore, RNA sequencing-based transcriptome analysis was used to map the metabolic pathways of the two strains and explore their explanatory potential for N preferences.ResultsThe results showed that strain M6-3 preferred to utilize NH4+ while strain M7-15 preferred to utilize NO3−. Although both strains shared similar nitrogen metabolic pathways, the differential expression of the glutamine synthetase-coding gene glnA played a crucial role in regulating their inorganic N preferences. This inconsistency in glnA expression may be attributed to GlnR, a global regulator of nitrogen utilization.DiscussionThis research strengthens the theoretical basis for exploring the underlying causes of differential preferences for inorganic N forms and provided key clues for screening functional microorganisms to ultimately enhance inorganic nitrogen use efficiency.